CARDIAC SURGERYInterventional treatment of moderate and severe mitral stenosis - Bochenek, Tomasz; Lelek, Michał; Mizia, Magdalena; Grabka, Marek; Rybicka-Musialik, Anna; Mizia-Stec, Katarzyna (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Mitral valve stenosis (MS) is becoming relatively rare. However, it was revealed in 12.1% of Euro Heart Survey participants suffering from single native left-sided valve diseases; most of these MS cases were rheumatic in origin. Echocardiographic study is a gold diagnostic standard for MS, and it includes transthoracic, transesophageal, and three dimensional evaluation. Accurate echocardiographic assessment has therapeutic implications. Interventional treatment should be considered in symptomatic patients with moderate to severe mitral stenosis (mitral valve area [MVA] ≤ 1.5 cm 2 ). Currently, percutaneous mitral commissurotomy (PMC) is the recommended method of treatment; the safety and efficacy of this procedure are particularly dependent on echocardiographic evaluation. According to the current ESC guidelines, a surgical approach is recommended primarily in cases in which there are contraindications to PMC. In the study presented below, we describe the current guidelines for the interventional treatment of the defect, the practical aspects of qualifying patients for PMC, and the rules for performing PMC.